Mapping vulnerability to extreme heat events: lessons from metropolitan Chicago. Issue 6 (12th May 2019) - Wilson, Bev; Chakraborty, Arnab
Abstract : In this paper, we develop an approach for identifying the location of populations most vulnerable to extreme heat events and how those locations change over time. We scan the literature on measuring vulnerability, especially sensitivity and adaptive capacity of populations. We employ Census data for metropolitan Chicago for the years 1990, 2000, and 2010, and maximum likelihood factor analysis to derive an index and map the distribution of Census tracts where residents exhibit greater sensitivity and/or lower adaptive capacity to extreme heat. Our findings show a pattern of deconcentration and decentralization of these populations within the city and region over time, with gentrification and the suburbanization of poverty trends observed in many US metropolitan regions as possible contributing factors. Finally, we discuss the implications of these findings for planning efforts in the study area and offer suggestions for further research.